Evaluation of Disulfide Bond Position to Enhance the Thermal Stability of a Highly Stable Single Domain Antibody - Zabetakis, Dan; Olson, Mark A.; Anderson, George P.; Legler, Patricia M.; Goldman, Ellen R. (PloS one, 2014)
Single domain antibodies are the small recombinant variable domains derived from camelid heavy-chain-only antibodies. They are renowned for their stability, in large part due to their ability to refold following thermal or chemical denaturation. In addition to refolding after heat denaturation, A3, a high affinity anti-Staphylococcal Enterotoxin B single domain antibody, possesses a melting temperature of ∼84°C, among the highest reported for a single domain antibody. In this work we utilized the recently described crystal structure of A3 to select locations for the insertion of a second disulfide bond and evaluated the impact that the addition of this second bond had on the melting temperature. Four double-disulfide versions of A3 were constructed and each was found to improve the melting temperature relative to the native structure without reducing affinity. Placement of the disulfide bond at a previously published position between framework regions 2 and 3 yielded the largest improvement (>6°C), suggesting this location is optimal, and seemingly provides a universal route to raise the melting temperature of single domain antibodies. This study further demonstrates that even single domain antibodies with extremely high melting points can be further stabilized by addition of disulfide bonds.